100 cases in radiology - Thomas, Robert; Connolly, James; Burke, Christopher (London : Hodder Arnold, 2012)
This book will teach students and junior doctors to recognize important conditions from radiological images, and to develop their diagnostic and management skills, in a format that encourages self-directed learning, clinical thinking and problem-solving
Deteriorating shortness of breath in a smoker The breathless asthmatic An icy fall Difficulty swallowing A mechanical fall in an elderly patient Jaundice following cholecystectomy Heartburn, epigastric pain and a cough Lines, catheters and tubes on a radiograph Weakness and slurring while out for a drink Back pain relieved only by aspirin A persistent cough in an ex-smoker A retired schoolmaster with progressive breathlessness Numb right arm Right upper abdominal upper pain Infant with clicking hips Painful wrist after falling Constipation in a woman with known ovarian tumour Thirty-year-old man with headache Persistent cough Chest pain and dyspnoea Young man with neck swelling Collapse and possible seizure Premature neonate with abdominal distension Young child with painful arm Acute epigastric pain Man with atypical chest pain Young woman with shortness of breath and chest pain Chest discomfort and dyspnoea Skateboarder with a painful foot Left-sided loin pain Unable to bear weight after a cycling accident Strange bone appearance after falling Lower back pain Vomiting baby boy Painless haematuria Sudden onset weakness in an 80-year-old woman Young man with ankle pain Painful shoulder Chest pain after falling Swelling of the big toe A young man with progressive dyspnoea on exertion Pain on deep inspiration An elbow injury Pain in the hand following a punching injury A fall on the hand and pain in the wrist Shortness of breath and pleuritic chest pain A new arrival with cough and a fever A seatbelt injury A device in the pelvis A cardiac abnormality A mirror image A distended and painful abdomen Bloody sputum and weight loss A soft fluctuant lump Abdominal distension and shifting dullness A painful hand A retired construction worker with a cough Distended abdomen and unable to pass gas Torrential haematemesis An incidental finding on chest radiograph A worried nurse in intensive care Young man with abdominal pain Skin plaques and achy hands Teaching sport can be a headache at times A chesty infant Difficulty in swallowing Pregnant woman with vomiting Infant with a head injury Abdominal distension in a woman with ovarian cancer A woman with a breast lump A rising creatinine Neck pain after falling A young man with back pain A child with an injury A renal tract abnormality Shooting leg pain following lifting A chronic productive cough General fatigue and weakness A cervical spine injury following a horse riding accident Abdominal pain and diarrhoea in a 28-year-old woman Pain in the left wrist following a fall A known case of inflammatory bowel disease A tourist from New Zealand Spontaneous nose bleeds in a young person Abdominal weight gain and distension despite dieting Left mid zone crackles Traumatic injury to a farmer's foot An accountant with abdominal pain Pain in a lady with breast cancer Headache and visual field defects A claudicant with worsening leg pain Normal variant on a chest radiograph Flank pain and haematuria Patient with an intractable headache An unwell patient with a rash Chest wall swelling and a pleural effusion Chest wall deformity in a pacemaker patient Sudden onset back pain in a 72-year-old woman Constipation and colicky abdominal pain An ankle injury
Keywords: Radiology, Medical -- Case studies